Strategi Positif dalam Mengatasi Tantrum Pada Anak Usia Dini - Imrotul Ummah; Pamuji (Student Scientific Creativity Journal, 2024)
Tantrums in early childhood are a phenomenon that often causes worry and stress for many parents. However, dealing with tantrums is not an easy task and often tests parents’ patience and emotional resilience. Early childhood is at a stage of development where they are starting to learn to recognize and express their emotions. Lack of language skills and managing emotions makes them vulnerable to experiencing frustration which leads to tantrums. Therefore, it is important for parents to understand the causes of tantrums and know how to deal with them positively and constructively. This research uses a library research design that relies on primary data in the form of literature or previous research related to strategies for dealing with tantrums. The researcher carefully read the data sources. to identify parental parenting patterns on children’s emotional stability. The information collected is then used as a guideline for educators’ synergistic efforts in dealing with tantrums, so that they can overcome tantrums that often occur in everyday life. This research uses library sources, including research results in the form of books, journals, articles and other relevant sources. This article concludes by analyzing the data obtained from these sources and drawing conclusions. Based on the results of the theoretical study analysis, it can be concluded that a positive strategy for dealing with tantrums in early childhood is to (1) Recognize the factors that cause Tantrums including ( a) Child factors, namely the obstruction of the child’s desire to get something (b) Parental factors or parenting style. Parental parenting styles influence the emergence of tantrums (c) children’s needs that are not met. and (2) Get to know efforts to overcome tantrums. (a) Parents and educators can prevent this from happening by being aware of children’s habits and knowing exactly when tantrums occur. (b) When a tantrum occurs, parents and educators should try to remain calm and control emotions. (c) After the tantrum is over, parents and educators should provide a sense of calm to the child, not punish or strengthen. (d) Parents and educators can minimize children’s anger and ensure the safety of children and other people. (e) If anger causes confusion, immediately move the child to a safe place or away from other children. (f) Parents Educators can also observe children closely to observe when anger occurs most often. (g) If the tantrum occurs again, handle it with a time out